India’s Fantasy in British ‘Heritage Films’: Analysis of a Passage to India - Valančiūnas, Deimantas (Literatūra, 2015)
This article deals with the reconfiguration of the colonial discourse and imagining the ‘Other’ in Britishheritage films and the analysis of David Lean’s film A Passage to India (1984)-an adaptation of F.M. Forster’s novel of the same title and a representative of a specific subgenre of the ‘heritage films’, known also as the ‘Raj revival’. The analysis of Lean’s A Passage to India is carried out in relation to the ‘Thatcherite’ era, conservative politics in Britain, and the ideologically constructed nostalgic gaze to the colonial past. As the analysis of the film has showed, the film is rather ambiguous. On the one hand, the film displays a critical attitude towards the Empire and emphasizes the brutality and inconsistency of the colonial regime in India, while on the other hand it invites the spectators to enjoy India as a nostalgic colonial spectacle and constructs it through the sexualisation and orientalisation of the country. The analysis has also showed that the film recharges its characters with an erotic content. The film A Passage to India eroticises the Indian man, where the character of Aziz is constructed as a man radiating a dangerous sexuality, which may lead to painful psychopathological consequences when encountered by a British woman – a discourse which becomes relevant once again in relation to the anti-immigration politics of the ‘Thatcherite’ Britain of the ’80s.